Early Insertion of Intra-Aortic Balloon Pump after Cardiac Arrest on Acute Coronary Syndrome Patients: A Randomized Clinical Trial - Firdaus, Isman; Yuniadi, Yoga; Andriantoro, Hananto; Boom, Cindy Elfira; Harimurti, Kuntjoro; Romdoni, Rochmad; Kusmana, Dede (Cardiology and Cardiovascular Medicine, 2019)
Background: The need for mechanical circulatory support to improve organ perfusion may be considered in the management of post cardiac arrest syndrome patients. Intra-Aortic Balloon Pump (IABP) is the most available and convenient used mechanical circulation aid especially in developing countries such as Indonesia. Objectives: This study aimed to find out whether early insertion of IABP can reduce in-hospital mortality, length of stay, cell death markers, and improving lactate clearance of cardiac arrest patients due to acute coronary syndrome (ACS). Methods: A randomized trial conducted in National Cardiovascular Center Harapan Kita (NCCHK) Hospital from October 2017–December 2018. Inclusion criteria were all post cardiac arrest due to ACS patients aged 18–75 years. Exclusion criteria were history of stroke, anisocoric pupil, previous IABP use, aortic regurgitation, Brugada syndrome, and congenital long QT syndrome. Primary outcome was in-hospital mortality analyzed with cox regression analysis with intention-to-treat principle. Results: A total of 60 post cardiac arrest due to ACS patients, 30 in intervention group and 30 controls included in this study. In hospital mortality of intervention group vs control was 18 (60%) vs. 17 (56.67%) respectively ([p = 0.793; hazard ratio 1.29; [CI] 95% 0.66–2.52). There was no differences in length of stay, cell death marker or lactate clearance in both group. Conclusion: Early insertion of IABP did not reduce in hospital mortality, length of stay, cell death marker or improve lactate clearance in post cardiac arrest patient due to ACS.